1999
DOI: 10.1038/sj.bjp.0702671
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet function by catecholamines in the cerebral vasculature of the rabbit

Abstract: In-labelled platelets were monitored continuously in the cerebral and pulmonary vascular beds of anaesthetized rabbits. Dopamine can, depending upon the concentration, either potentiate or inhibit thrombin-induced platelet accumulation in the cerebral vasculature of rabbits by unknown mechanisms. The eects of speci®c adrenergic and dopaminergic receptor antagonists were tested upon dopamine's actions on intracarotid (i.c.) thrombin-induced (80 u kg 71 ) platelet accumulation in the cerebral vasculature. The ee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In vivo investigations reported that dopamine and dopamine receptor agonists can modify platelet function (Emerson et al 1997(Emerson et al , 1999. However, since the first reports of the presence of dopamine receptors in platelets De Keyser et al 1988), subsequent studies did not provide conclusive results (Boullin et al 1978;De Keyser et al 1989;Anfossi et al 1992Anfossi et al , 1993Dean et al 1992).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In vivo investigations reported that dopamine and dopamine receptor agonists can modify platelet function (Emerson et al 1997(Emerson et al , 1999. However, since the first reports of the presence of dopamine receptors in platelets De Keyser et al 1988), subsequent studies did not provide conclusive results (Boullin et al 1978;De Keyser et al 1989;Anfossi et al 1992Anfossi et al , 1993Dean et al 1992).…”
Section: Discussionmentioning
confidence: 96%
“…In vivo studies performed in rabbit cerebral and pulmonary vasculature have shown that dopamine modifies platelet aggregation as a function of concentration (Emerson et al 1997(Emerson et al , 1999. However, so far no conclusive evidence was provided on the expression of dopamine receptors by platelets and no information is available concerning dopamine receptor subtypes expressed by platelets.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dopamine receptors are expressed in many organs and tissues, and stimulation of the dopamine D 1 -like receptors prevents atherosclerosis via the inhibition of proliferation, migration and oxidation of VSMCs [12][13][14][15]. Dopamine D 1 -like receptors are present in VSMCs, platelets, lymphocytes and natural killer cells [33,34]. Our current study shows that both D 1 and D 5 receptors are expressed in macrophages.…”
Section: Discussionmentioning
confidence: 76%